К вопросу об эсхатологических представлениях Святителя Bикторина Петавийского и Псевдо-Bикторина Петавийского - Khandoga, Nikolai A. (Warszawskie Studia Teologiczne, 2018)
The eschatological views of the Victorinus of Poetovio and the Pseudo-Victorinus of Poetovio are set forth in their writings – the treatise On the Creation of the World, Commentary on the Apocalypse and the treatise On the Ten Virgins. Common to the two Latin exegetes is that they eagerly awaited the Last Judgment and the Second Coming of Christ, and also urged Christians daily to perform church obediences and to do as many good deeds as possible. At the same time, each of them taught in his own way how and when it should happen.Victorinus of Poetovio, as one of the Latin millenarists, in the treatise On the Creation of the World and Commentary on the Apocalypse taught that in the near future the Lord Jesus Christ must come to earth for the second time to reign with his chosen ones for a thousand years. A>er this, the Last Judgment will take place, on which a sentence will be handed down for unrepentant sinners and daily penitents who are righteous. The first awaits the eternal torment with the devil and his angels, and the second awaits eternal bliss with Christ and his angels.Pseudo-Victorinus of Poetovio, as one of the Latin non-millionaire writers, taught in the treatise On the Ten Virgins that in the indefinite future the Lord Jesus Christ must come to earth for the second time to judge unrepentant sinners and pardon every day the penitent righteous. A>er this, there will also come the eternal bliss of the righteous and the eternal torment of sinners.